A new deep-water goatfish of the genus Upeneus (Mullidae) from northern Australia and the Philippines, with a taxonomic account of U. subvittatus and remarks on U. mascareinsis - Uiblein, Franz; Mcgrouther, Mark (Zootaxa, 2012)
Upeneus stenopsis n. sp. is described based on four specimens collected off northern Australia and Quezon Island,Philippines, at depths between 165 to 275 m and compared with four closely related species: the deep-water dwellingUpeneus davidaromi (Red Sea) and U. mascareinsis (Western Indian Ocean) and the shallow Indo-West Pacific species,U. subvittatus and U. vittatus. The new species can be distinguished from all other Upeneus species by a narrow caudalpeduncle and a combination of morphometric and meristic characters. This is the first record of a deep-water goatfish ofthe genus Upeneus from the Pacific. A juvenile Upeneus collected off Quezon at 127–142 m depth was also assigned tothe new species and compared to four similar-sized (69–79 mm SL) specimens of U. mascareinsis. A diagnosis is providedfor U. subvittatus, along with evidence of its occurrence in the Eastern Indian Ocean and interspecific comparisons. Thecontinued need to screen scientific fish collections for the occurrence of undescribed species that have successfully colonized and adapted to the depth zone surrounding the ocean margin is outlined.